Collective effects in condensed matter physics - Kiselev, Vladimir V. (De Gruyter studies in mathematical physics, 2018)
This monograph offers a concise overview of the theoretical description of various collective phenomena in condensed matter physics. These effects include the basic electronic structure in solid state physics, lattice vibrations, superconductivity, light-matter interaction and more advanced topics such as martensitic transistions.